RANCANG BANGUN SISTEM AUTOMATED GUIDED VEHICLE (AGV) MENGGUNAKAN AGV LINE FOLLOWER BERBASIS FUZZY LOGIC CONTROL SEBAGAI PENENTU RUTE DAN BERAT BARANG - Mohammad, Luthfansyah; Aulia Istiqomah; Ardani, Hanif Satrya (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The Automated Guided Vehicle (AGV) is a robotic innovation designed to assist in the process of delivering goods in the logistics sector of a factory. The stability of an AGV's movement has a direct impact on the safety of the goods it transports. This research aims to overcome this problem by designing and implementing an AGV mapping control system using a Fuzzy Inference System. The Load cell sensor is used as system input to measure the weight of the load carried by the AGV. The data from this sensor is then processed by the Fuzzy Inference System to produce information about the load value carried by the AGV. The research results showed that the AGV could determine the destination post when goods were placed in the load cell sensor. When the AGV was running, it went to the destination post according to the weight of the goods, and an accuracy of 100% and an error level of 5% were obtained from testing the load cell sensor.